Ekonomi Kemakmuran Bersama: Indonesian Islamic Economic Thought of Kahrudin Yunus - Addiarrahman, Addiarrahman (Shirkah: Journal of Economics and Business, 2018)
This article preliminary explores a forgotten figure of defining concept of Indonesian Islamic economics, Kahrudin Yunus. Differ from other contemporary concepts; Yunus has generously framed sistem ekonomi kemakmuran bersama as a basic principle of Islamic economics. Although Yunus has courageously implanted such Arabic economic thinker as Baqr al-Shadr, the Indonesian political tension that infused capitalism and socialism in the middle of 1955 had imposed him to not define Islamic economics in narrow theological perspective, conversely, Yunus argued that Islamic economics must be built on the benefits of economic politics in order to constructing a democratic system. Yunus forgotten thought would have been a counter debate of contemporary Islamic economics today that somehow enforced the return of golden age of Islamic revival.   Keywords: Islamic economics, kemakmuran bersama, economic thinker